Formation of root silica aggregates in sorghum is an active process of the endodermis - Soukup, Milan (J Exp Bot, 2019)
Silica deposition in plants is a common phenomenon that correlates with plant tolerance to various stresses. Deposition occurs mostly in cell walls, but its mechanism is unclear. Here we show that metabolic processes control the formation of silica aggregates in roots of sorghum (Sorghum bicolor L.), a model plant for silicification. Silica formation was followed in intact roots and root segments of seedlings. Root segments were treated to enhance or suppress cell wall biosynthesis. The composition of endodermal cell walls was analysed by Raman microspectroscopy, scanning electron microscopy and energy-dispersive X-ray analysis. Our results were compared with in vitro reactions simulating lignin and silica polymerization. Silica aggregates formed only in live endodermal cells that were metabolically active. Silicic acid was deposited in vitro as silica onto freshly polymerized coniferyl alcohol, simulating G-lignin, but not onto coniferyl alcohol or ferulic acid monomers. Our results show that root silica aggregates form under tight regulation by endodermal cells, independently of the transpiration stream. We raise the hypothesis that the location and extent of silicification are primed by the chemistry and structure of polymerizing lignin as it cross-links to the wall.